2021
DOI: 10.1002/pbc.29415
|View full text |Cite
|
Sign up to set email alerts
|

18F‐FDG PET and PET/CT as a diagnostic method for Ewing sarcoma: A systematic review and meta‐analysis

Abstract: Purpose:The aim of this study was to evaluate the diagnostic accuracy of 18fluorodeoxyglucose-positron emission tomography ( 18 F-FDG PET) and PET/computed tomography (PET/CT) in imaging primary and metastatic lesions in Ewing sarcoma (ES).Methods: PubMed, Cochrane, Scopus, and Web of Science were searched for relevant studies. Data concerning 18 F-FDG PET/CT diagnostic accuracy were extracted and then analyzed using Open Meta-analyst software. Reported diagnostic accuracy outcomes included sensitivity, specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…18 F FDG PET/CT has shown to help to localize the primary sarcoma, its extension, metastasis specially the bony and pulmonary metastasis and to check the response to standard treatment available [8]. It also allows the detection of progression or regression and recurrence of disease prior to anatomic imaging [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…18 F FDG PET/CT has shown to help to localize the primary sarcoma, its extension, metastasis specially the bony and pulmonary metastasis and to check the response to standard treatment available [8]. It also allows the detection of progression or regression and recurrence of disease prior to anatomic imaging [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…The overall sensitivity for detecting lymph node metastases was 79.3% (95% CI: 58.7-91.2%) and the specificity was 97.9% (95% CI: 93.5-99.3%). Not surprisingly, the overall sensitivity for detecting lung metastases was low at 76.1% (95% CI: 61.4-86.5%), and the overall specificity was 92.4% (95% CI: 86.3-95.9%) [54].…”
Section: Ewing Sarcomamentioning
confidence: 92%
“…7 Additional reports have corroborated these findings. 8,9 Although many centers have access to FDG-PET, and data have demonstrated the superiority of FDG-PET over bone scintigraphy for the detection of bone metastases in these patients, 10 some centers without FDG-PET may continue to use bone scintigraphy or other modalities, such as whole-body MRI. Whereas FDG-PET-MRI is an active area of investigation, [11][12][13] and one study has demonstrated excellent concordance between PET-CT (sensitivity, 90.0%; specificity, 100%) and PET-MRI (sensitivity, 97.5%; specificity, 99.4%), 14 no firm conclusions can be made about the utility of FDG-PET-MRI at this time.…”
Section: Question 1: How Should Patients With Newly Diagnosed Es Be E...mentioning
confidence: 99%